Stabilisation of Lutein and Lutein Esters with Polyoxyethylene Sorbitan Monooleate, Medium-Chain Triglyceride Oil and Lecithin - Zala Gombač; Ilja Gasan Osojnik Črnivec; Mihaela Skrt; Katja Istenič; Andreja Knez Knafelj; Igor Pravst; Nataša Poklar Ulrih (Foods, 2021)
Lutein is a challenging compound to incorporate into food, as it is poorly soluble and unstable in aqueous solutions. In this study, the aim was to prepare stable encapsulates of lutein and lutein esters using feasible and straightforward techniques. Fine suspensions based on polyoxyethylene sorbitan monooleate and medium-chain triglyceride oil micelle-like units with 3.45% lutein esters or 1.9% lutein equivalents provided high encapsulation efficiencies of 79% and 83%, respectively. Lutein encapsulated in fine suspensions showed superior stability, as 86% was retained within the formulation over 250 days at 25 °C in the dark. Under the same storage conditions, only 38% of lutein remained in corresponding formulations. Higher encapsulation efficiencies were achieved with lecithin emulsions, at up to 99.3% for formulations with lutein, and up to 91.4% with lutein esters. In lecithin emulsions that were stored for 250 days, 17% and 80% of lutein and lutein esters, respectively, were retained within the formulations.